PRIMULA: A framework based on finite elements to address multi scale and multi physics problems - Soba, Alejandro (2018)
The PRIMULA code, a multi scale and multithreads open source framework based on finite elements applicable to the numerical resolution of partial differential equations is presented. PRIMULA is portable to LINUX/UNIX, where it is compiled with gfortran, and to WINDOWS, compiled in the Visual Studio environment. It can be compiled to run in series, with shared memory under the Standard OPENMP, in a distributed environment under Standard MPI and on hybrid systems, with a compilation that combines MPI-OPENMP. The code was tested with non-linear problems in a 16 cores Intel Xeon (R) E5-2630 v3 multiprocessor of 2.4 GHz and in TUPAC, with 4 × Hexadeca core AMD Opteron 6276s processors. This paper presents results of scalability and computation times of some of the multiple tests to which it was submitted.